Greenbug feeding-induced resistance to sugarcane aphids in sorghum - Puri, Heena; Ikuze, Edith; Ayala, Jessica; Rodriguez, Isabella; Kariyat, Rupesh; Louis, Joe; Grover, Sajjan (Frontiers in Ecology and Evolution, 2023)
Plants are attacked by multiple insect-pest species and insect herbivory can alter plant defense mechanisms. The plant defense responses to a specific herbivore may also contribute to the herbivore growth/survival on plants. Feeding by one insect species can modulate the plant defenses, which can either facilitate or hamper the colonization of subsequent incoming insects. However, little is known about the effect of sequential herbivory on sorghum plants. In this study, we demonstrate that a specialist aphid, sugarcane aphid (SCA; Melanaphis sacchari) grows faster on sorghum than a generalist aphid species, greenbug (GB; Schizaphis graminum). We also determined how the pre-infestation of SCA on sorghum affected the invasion of GB and vice-versa. Our sequential herbivory experiments revealed that SCA reproduction was lower on GB-primed sorghum plants, however, the reverse was not true. To assess the differences in plant defenses induced by specialist vs generalist aphids, we monitored the expression of salicylic acid (SA) and jasmonic acid (JA) marker genes, and flavonoid biosynthetic pathway genes after 48 hours of aphid infestation. The results indicated that GB infestation induced higher expression of SA and JA-related genes, and flavonoid pathway genes (DFR, FNR, and FNSII) compared to SCA infestation. Overall, our results suggested that GB-infested plants activate the plant defenses via phytohormones and flavonoids at early time points and hampers the colonization of incoming SCA, as well as explain the reproductive success of SCA compared to GB.